2004
DOI: 10.1159/000075572
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Renal Injury in C3- and C4-Deficient Mice: A Histological and Functional Study

Abstract: Background: Complement deficiency predisposes to autoimmune renal disease. Since complement deficient mice are increasingly used to study the immunopathogenesis of renal disease we have determined whether mice deficient in C3 or C4 are susceptible to spontaneous immune-mediated renal injury. Methods: C3-deficient, C4-deficient and complement-sufficient, wild-type mice were maintained in standard conditions for 1 year at which stage renal function, renal histology, circulating antibody and autoantibody levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This association has also been demonstrated in previous studies in animal models. 34,35 The neutrophil recruitment in kidney and proteinuria were alleviated in the C4-deficient mice with either anti-glomerular basement membrane (GBM)-mediated nephritis 36 or acute nephrotoxic serum nephritis. 37 Though C3 is an essential factor in complement system, the analyses of the patients with low C3 levels and the subgroup analysis showed that C3 levels were not significantly associated with renal injury at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…This association has also been demonstrated in previous studies in animal models. 34,35 The neutrophil recruitment in kidney and proteinuria were alleviated in the C4-deficient mice with either anti-glomerular basement membrane (GBM)-mediated nephritis 36 or acute nephrotoxic serum nephritis. 37 Though C3 is an essential factor in complement system, the analyses of the patients with low C3 levels and the subgroup analysis showed that C3 levels were not significantly associated with renal injury at baseline.…”
Section: Discussionmentioning
confidence: 99%